Cho $F(x)=\dfrac{1}{2x^2}$ là một nguyên hàm của hàm số $\dfrac{f(x)}{x}$. Tìm nguyên hàm của hàm số $f'(x)\ln x$.
![]() | $\displaystyle\displaystyle\int f'(x)\ln x\mathrm{\,d}x=-\left(\dfrac{\ln x}{x^2}+\dfrac{1}{x^2}\right)+C$ |
![]() | $\displaystyle\displaystyle\int f'(x)\ln x\mathrm{\,d}x=\dfrac{\ln x}{x^2}+\dfrac{1}{x^2}+C$ |
![]() | $\displaystyle\displaystyle\int f'(x)\ln x\mathrm{\,d}x=-\left(\dfrac{\ln x}{x^2}+\dfrac{1}{2x^2}\right)+C$ |
![]() | $\displaystyle\displaystyle\int f'(x)\ln x\mathrm{\,d}x=\dfrac{\ln x}{x^2}+\dfrac{1}{2x^2}+C$ |
Chọn phương án C.
Vì $F(x)=\dfrac{1}{2x^2}$ là một nguyên hàm của hàm số $\dfrac{f(x)}{x}$ nên $$\dfrac{f(x)}{x}=F'(x)=-\dfrac{1}{x^3}\Rightarrow f(x)=-\dfrac{1}{x^2}.$$
Mặt khác, ta cũng có $\displaystyle\int\dfrac{f(x)}{x}\mathrm{\,d}x=F(x)=\dfrac{1}{2x^2}$.
Đặt $\begin{cases}
u=\ln x\\ v'=f'(x)
\end{cases}\Rightarrow\begin{cases}
u'=\dfrac{1}{x}\\ v=f(x)
\end{cases}$. Khi đó $$\begin{aligned}
\displaystyle\int f'(x)\ln x\mathrm{\,d}x&=f(x)\ln x-\int\dfrac{f(x)}{x}\ln x\mathrm{\,d}x\\
&=-\dfrac{1}{x^2}\cdot\ln x-\dfrac{1}{2x^2}+C\\
&=-\left(\dfrac{\ln x}{x^2}+\dfrac{1}{2x^2}\right)+C.
\end{aligned}$$